The self-assembling camptothecin-tocopherol prodrug: An effective approach for formulating camptothecin. (September 2015) - Lu, Jianqin; Liu, Chuang; Wang, Pengcheng; Ghazwani, Mohammed; Xu, Jieni; Huang, Yixian; Ma, Xiaochao; Zhang, Peijun; Li, Song
Abstract: Camptothecin (CPT) is a potent antitumor agent and functions via inhibiting the activity of topoisomerase I during DNA replication. However, the clinical application of CPT has been greatly hindered by its extremely poor solubility, the instability of its active lactone ring in blood stream, as well as the non-specific toxicity to normal tissues. In addition, most of the formulations developed so far are not applicable for formulating CPT. In this study, two novel CPT prodrugs were developed by conjugating CPT to α-tocopherol via a carbonate ester bond (CPT-VE) or disulfide linkage (CPT-S-S-VE). Both CPT prodrugs were able to self-assemble into nanofibers with the facilitation of a PEG5K -Fmoc-VE2 -based nanomicellar carrier. Both prodrug nanoassemblies exhibited excellent stability. Fluorescence quenching, UV absorbance, and FT-IR studies demonstrated strong interactions between carrier and prodrugs, including hydrophobic interaction, π–π stacking, as well as hydrogen bonding. NMR studies suggested that prodrugs were successfully incorporated into PEG5K -Fmoc-VE2 during self-assembly process. In vitro, PEG5K -Fmoc-VE2 /CPT-S-S-VE presented significantly higher level of cytotoxicity on tumor cells compared to PEG5K -Fmoc-VE2 /CPT-VE. Biodistribution study showed that CPT-S-S-VE formulated in PEG5K -Fmoc-VE2 micelles was effectively converted to parent CPT following delivery to tumor tissues. Finally, PEG5K -Fmoc-VE2 /CPT-S-S-VE nanofibers showed superior tumor growth inhibition in an aggressive murine breast cancer model (4T1.2).